Biologic Augmentation of the Ulnar Collateral Ligament in the Elbow of a Professional Baseball Pitcher - James K. Hoffman; Nicole M. Protzman; Amit D. Malhotra (Case Reports in Orthopedics)
Tears of the ulnar collateral ligament (UCL) of the elbow are common injuries in overhead athletes. Although surgical reconstruction of the UCL has improved outcomes, not all athletes return to their previous level of competition and when this goal is achieved, the time required averages one to two years. Therefore, additional techniques are needed to further improve return to play and the rate of return to play in overhead athletes. A construct comprising a dermal allograft, platelet rich plasma (PRP), and mesenchymal stem cells (MSCs) has been shown to successfully improve healing in the rotator cuff. Given the promising provisional findings, we postulated that this construct could also improve healing if applied to the UCL. Therefore, the purpose of the present report was to examine the feasibility of utilizing a dermal allograft, PRP, and MSC construct to augment UCL reconstruction in a professional baseball pitcher. No complications were encountered. Although limited to minimal follow-up, the patient has demonstrated excellent progress and has returned to activity.